2020
DOI: 10.3390/brainsci11010026
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms among Middle-Aged Women—Understanding the Cause

Abstract: Menopause is an important event in a woman’s life associated with hormonal changes that play a substantial role in the functioning of her body. A decline in the level of estrogens contributes to depressive symptoms and mood disorders during this period. The severity of depressive symptoms experienced by middle-aged women depends on many factors, including sociodemographic data (e.g., menopause, employment status, and marital status) and genetic variables (MAO-A and 5-HTT gene polymorphisms). In order to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…A reason for this sex difference is that, in menopausal women, a reduction in sex hormones is associated with hypertension [ 36 , 37 , 38 ] and depression [ 39 , 40 ]. An investigation of healthy Polish women in various stages of menopause by Cybulska et al [ 41 ]. showed that specific genotypes are related to depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A reason for this sex difference is that, in menopausal women, a reduction in sex hormones is associated with hypertension [ 36 , 37 , 38 ] and depression [ 39 , 40 ]. An investigation of healthy Polish women in various stages of menopause by Cybulska et al [ 41 ]. showed that specific genotypes are related to depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in some studies, the MAOA-H/H genotype was considered implicated; 62,63,65,66,[84][85][86] whereas in other studies, the risk genotype identified was MAOA-L/L. 64,87,88 Such contradictory results may reflect issues with rather small sample sizes, the use of different instruments, and consideration of varying covariates and random effects included (or not) in the models.…”
Section: Influence Of Genotype and Sex On Anxiety Toward Mathematicsmentioning
confidence: 99%
“…On the one hand, an association of the MAOA‐L genotype and externalizing behavior disorders, including impulsivity, aggressiveness, and antisocial behavior, has been consistently reported for males 10,41,42,45,48,59–61 . On the other hand, although less consistently, the MAOA‐LPR promoter polymorphism has been associated with decreased emotional stability and internalizing disorders, such as depression and anxiety in women 62–66 . Considering what was discussed above, we pursued the hypothesis that the MAOA‐LPR polymorphism may also contribute to explaining the female susceptibility to MA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hormonal changes taking place in a woman's body significantly affect everyday functioning; moreover, there are many controversies regarding the role of menopause in the development of depression and anxiety [4]. It is worth noting that although there is an increased risk of clinical and subclinical depression during the period of reduced estrogen levels, its occurrence should not be directly attributed to menopause, but to various factors, including neurotransmitters, sociodemographic variables [17], psychosocial variables [18], personality traits [19] or genome [20,21].…”
Section: Introductionmentioning
confidence: 99%